Derivation and its effect on the Qur'anic meaning through Tafsir Albahr Almuhit by Abu Hayyan Al-Andalusi - Elhag, Fathelrahman Elnaeem Adam (Arab Journal for Sciences and Research Publishing, 2021)
This study dealt with one of the important phenomena that actively contributed to the development of language, directing the linguistic and lexical connotations of the Qur’anic vocabulary. In order to reach the meanings that fall under it that had an effective effect on enriching the science of interpretation of the Noble Qur’an, and it is the phenomenon of (the derivation) that endowed the vocabulary of the language and the Holy Qur’an with breadth in its highest meanings, and carried it from the connotations that renewed the Arabic word with a structure and meaning, thus opening the horizons of breadth and inclusion, through Tafsir Albahr Almuhit by Abu Hayyan Al-Andalusi.This study came in two chapters: The first dealt with the derivation: its importance and types. It came in two topics: the first dealt with the importance of derivation, dealing with the definition of derivation as a language and idiom, and the second topic dealt with the types of derivation. The second chapter deals with the derivation and its relationship with meaning.Then the conclusion came to include a set of findings and facts that were dealt with in this study, and the recommendation of researchers in this field to pay attention to the issue of derivation because of its impact on the development of linguistic and Quranic meaning alike, followed by the margins, and then the references that benefited from it.
Keywords: Etymology; The Quranic Meaning; Interpretation of Al-Bahr Al-Muhit